Diabetes mellitus and its association with chronic depression in adults in the Peruvian population - Chang Espejo , Sergio Suijon (2024)
Objective: To determine the association between diabetes mellitus and chronic depression in adults in the Peruvian population. Materials and methods: A quantitative, observational, cross-sectional and correlational study was carried out, based on the data collected by the 2020 Encuesta Demográfica y de Salud Familiar (ENDES – Demographic and Family Health Survey, 2020). The sample was made up of 14,245 adults; depression was considered as a dependent variable (with depression/without depression), and the independent variables were diabetes mellitus (Yes/No), wealth index (the poorest, poor, middle class, rich, the richest), education (kindergarten-preschool and primary, secondary, non-university higher, university higher and graduate), alcoholism (Yes/No), area of residence (urban/rural). The program used for the statistical analysis was IBM SPSS: Release 23. A univariate data analysis was carried out by determining the frequencies and percentages. Subsequently, in the analytical phase, bivariate and multivariate analyses by logistic regression were used to evaluate the strength of the association between the variables (p < 0.05). Results: A total of 15.7 % of adults between 27 and 59 years of age experienced chronic depression. Furthermore, the bivariate analysis revealed an association between the outcome variable and covariates—diabetes mellitus, level of education and wealth index—(p < 0.05). Depression is more common in lower socioeconomic groups, with higher rates among the poor (16.63 %) and less educated population, especially in those with kindergarten, preschool and primary education (18.88 %). In contrast, the rich and richest classes show lower rates of depression (15.27 % and 12.04 %, respectively). On the other hand, in the multivariate analysis, the risk estimation was carried out, and it was found that having diabetes increased the risk of suffering depression by 1.66 times compared to patients who did not have diabetes. Conclusions: There is an association between chronic depression and diabetes mellitus in the adult population aged 27 to 59 years; in addition, a low wealth index and a lower level of education are risk factors for chronic depressive disorder.